Dynamics of nucleosome remodelling by individual ACF complexes - Blosser, Timothy R. (2009)
The ATP-utilizing chromatin assembly and remodelling factor (ACF) functions to generate regularly spaced nucleosomes, which are required for heritable gene silencing. The mechanism by which ACF mobilizes nucleosomes remains poorly understood. Here we report a single-molecule FRET study that monitors the remodelling of individual nucleosomes by ACF in real time, revealing previously unknown remodelling intermediates and dynamics. In the presence of ACF and ATP, the nucleosomes exhibit gradual translocation along DNA interrupted by well-defined kinetic pauses that occurred after approximately 7 or 3 – 4 base pairs of translocation. The binding of ACF, translocation of DNA, and exiting of translocation pauses are all ATP-dependent, revealing three distinct functional roles of ATP during remodelling. At equilibrium, a continuously bound ACF complex can move the nucleosome back-and-forth many times before dissociation, indicating that ACF is a highly processive and bidirectional nucleosome translocase.